Guidelines Of Islamic Corporate Social Responsibility Of Islamic Bank In Thailand - Ekarat, Sitisan (2018)
Researchers have infrequently researched the concept of Islamic corporate social responsibility. Their researches on corporate social responsibility (CSR) in Islam are mostly on the theoretical part which is concerned about Islamic CSR principles and Islamic CSR framework. However, Islamic CSR framework and Islamic CSR principles could not apply in Islamic financial institutions without guidelines for practice. Thus, Islamic CSR guidelines of Islamic financial institutions were needed to identify. The general objective of this study was to propose Islamic CSR guidelines of an Islamic bank in Thailand. The second objective was to measure the practice of an Islamic bank in Thailand on CSR and to analyse the possibility of applying the proposed Islamic CSR guidelines into an Islamic bank in Thailand. In this research, a purposive sampling technique was used to select the six informants who are involved with CSR of an Islamic bank in Thailand such as a CSR representative of an Islamic bank, a director of an Islamic bank, a shari’ah advisory board of an Islamic bank for an interview on CSR in the Islamic bank. Also, the questionnaire was distributed and answered by four respondents, who are a shari’ah advisory, an expert person in Islamic finance and CSR representative of an Islamic bank, to find their opinions on the proposed Islamic CSR guidelines. This research was conducted qualitatively. The content analysis was chosen to analyse these data